Treatment of cutaneous leishmaniasis by topical 25% podophyllin solution (single, blinded, therapeutic, controlled study) - Khalifa E. Sharquie; Adil A. Noaimi; Ahmed G. Al-Ghazzi (Wolters Kluwer Medknow Publications, 2015)
Background: There are many therapies that had been used to treat cutaneous leishmaniasis (CL). Objective: To evaluate the effectiveness of topical 25% podophyllin solution in treatment of CL. Patients and methods: Sixty-five patients with acute CL enrolled in this study, which was done in the Department of Dermatology, Baghdad Teaching Hospital, Baghdad, during January 2008-April 2009.The total number of lesions was 124 and duration of lesions ranged from 3 to 12(6.84 ± 2.902) weeks. The size of lesions ranged from 0.5 to 3(1.75 ± 1.81) cm. Diagnosis was confirmed by biopsy and smear. Lesions were divided into two groups with matching of type and size of lesions Group A treated with topical 25% podophyllin solution once weekly for number of sessions ranged from 3 to 6(4.51 ± 0.85) sessions. Group B was left untreated as a control group. Follow up was every 2 weeks for 8 weeks. Results: The total number of lesions was 120:79(65.84%) were ulcerated and 41(34.16%) were dry and 25(40.32%) patients had single lesion while 37(59.677%) patients had multiple lesions. Group A: 51(85%) lesions out of 60 lesions had cure with number of sessions ranging from 3 to 6(5.137 ± 0.9385) sessions. Group B: no lesion was cured. Conclusions: Topical 25% podophyllin is a new effective topical therapy for CL, with few side effects.